INTEGRASI PRINSIP ETIKA QUR’ANI DALAM TEETIKA QUR’ANI DALAM MANAJEMEN ORGANISASI DAKWAH MODERNORI ORGANISASI MODERN - Novandika, Dida; Mahmud, Hamidullah (Jurnal Al-Hikmah: Jurnal Dakwah, 2025)
Globalization and digital transformation have significantly reshaped the governance of Islamic da’wah institutions, creating an urgent need to reinforce ethical and spiritual accountability in organizational management. This study aims to examine the integration of Qur’anic ethical values amanah (trust), musyawarah (deliberative participation), ‘adl (justice), and muhasabah (self-evaluation) into the management of modern da’wah organizations. Employing a qualitative approach through library research, this study applies thematic analysis to scholarly works published over the past five years that address Islamic ethics and da’wah management. The findings reveal that amanah establishes the moral foundation for accountability and transparency; musyawarah strengthens participatory decision-making and institutional legitimacy; ‘adl ensures distributive and procedural justice in serving the ummah; and muhasabah functions as a reflective mechanism for sincerity and performance improvement in da’wah activities. The integration of these four principles forms an ethical management paradigm that harmonizes the spiritual, social, and professional dimensions of da’wah organizations. The study concludes that the application of Qur’anic ethics not only reinforces moral legitimacy but also enhances public trust and organizational sustainability. This conceptual review provides a theoretical foundation for developing a Qur’anic value-based da’wah governance model grounded in maqāṣid al-sharī‘ah and social responsibility.Keywords: Qur’anic Ethics; Da’wah Management; Accountability; Organizational Justice.[Fenomena globalisasi dan transformasi digital telah mendorong perubahan mendasar dalam tata kelola lembaga dakwah, sehingga menuntut penguatan prinsip etika dan akuntabilitas spiritual dalam pengelolaan organisasi. Dalam konteks ini, kajian ini bertujuan untuk menelaah integrasi nilai-nilai etika Qur’ani amanah (kepercayaan), musyawarah (partisipasi deliberatif), ‘adl (keadilan), dan muhasabah (evaluasi diri) dalam manajemen organisasi dakwah modern. Penelitian ini menggunakan pendekatan kualitatif dengan metode kajian pustaka (library research) melalui analisis tematik terhadap literatur ilmiah lima tahun terakhir yang berkaitan dengan etika Islam dan manajemen dakwah. Hasil kajian menunjukkan bahwa amanah membentuk dasar akuntabilitas moral dan transparansi lembaga dakwah; musyawarah memperkuat partisipasi dan legitimasi pengambilan keputusan; ‘adl memastikan keadilan distributif dalam pelayanan umat; sementara muhasabah menjadi mekanisme reflektif untuk menjaga keikhlasan dan kualitas kinerja dakwah. Integrasi keempat prinsip ini melahirkan paradigma manajemen dakwah etis yang menyeimbangkan orientasi spiritual, sosial, dan profesional lembaga. Kajian ini menyimpulkan bahwa penerapan etika Qur’ani dalam organisasi dakwah bukan hanya memperkuat legitimasi moral, tetapi juga meningkatkan kepercayaan publik dan keberlanjutan lembaga. Penelitian ini memberikan dasar konseptual bagi pengembangan model tata kelola dakwah berbasis nilai Qur’ani yang berorientasi pada maqāṣid al-syarī‘ah dan tanggung jawab sosial umat].Kata Kunci: Etika Qur’ani; Manajemen Dakwah; Akuntabilitas; Keadilan Organisasi.